Analisis Faktor Yang Mempengaruhi Fungsi Intermediasi Perbankan Syariah Di Indonesia - Eflinda, Eva (Eko dan Bisnis: Riau Economic and Business Review, 2016)
Conditions increase national economic growth, there is still a significant impact on improving the local economy.One indication can be seen from the still high level of unemployment in 2015 ago. This happens because the complaint businessmen who felt the difficulty of obtaining a capital injection of banking as an important resource to increase their production capacity. So that the Indonesian banking intermediation is still questionable. Specialized in Islamic banking intermediation role can be seen from the indicators Financing to Deposit Ratio (FDR). FDR Islamic banking in 2015 showed a decrease from previous years. This indicates a growing gap between the funds collected far with funds channeled through financing in Islamic banking. Thus it is possible to make a research on the analysis of the factors that may affect the banking intermediation function of Islamic banking. This study aims to identify factors that influence the function of intermediation of Islamic banking in Indonesia for the period 2011 to 2015. Another aim was to determine which variable most dominant influence on Islamic banking intermediation in Indonesia 2011-2015. The research object of this thesis is that Islamic banking industry is composed of Islamic Banks and Sharia Business Unit which operates from 2011 to 2015 totaling 34 units, consisting of 12 commercial banks and 22 Islamic Sharia Business Unit. The number of samples in this study are as many as 31 Islamic banks to test all members of the population as the sample in the study. The analytical tool used in this study is a model of "distributed-lag model". In this model, the analysis carried out is multiple linear regression analysis, correlation, calculation of the value of the coefficient of determination, and hypothesis testing by t-test and F-test. The conclusion of the analysis that has been conducted on the independent variables ie Non Perforning Finance (NPF), Bank Indonesia Certificates Sharia (SBIS), Gross Domestic Product (GDP) and the Composite Stock Price Index (CSPI) on the dependent variable, namely Financing to Deposit Ratio ( FDR) is, There is a significant relationship between the NPF, SBIS, GDP and JCI together against FDR. Partially, NPF has a significant positive relationship with FDR, while the SBIS and JCI have a significant negative relationship with FDR, and for the GDP no significant relationship with FDR. From some of the variables that have a relationship with FDR, was JCI with a significant level of 0.905 or 90.5%.